Wnt-Responsive Odontoblasts Secrete New Dentin after Superficial Tooth Injury. (August 2018) - Zhao, Y.; Yuan, X.; Liu, B.; Tulu, U.S.; Helms, J.A.
The objective of our experiments was to identify new therapeutic strategies to stimulate dentin formation in an adult tooth. To address this objective, we evaluated dentin production in 2 acute trauma models: one involving a pulp exposure and the other involving a superficial dentin injury. Molecular, cellular, and histologic analyses revealed that in response to a severe injury, where the pulp is exposed to the oral cavity, cell death is rampant and the repair response initiates from surviving pulp cells and, to a lesser extent, surviving odontoblasts. When an injury is superficial, as in the case of a dentin injury model, then disturbances are largely confined to pulp tissue immediately underneath the damaged dentin tubules. We found that the pulp remained vital and innervated; primary odontoblasts upregulated HIF1α; and the rate of mineralization was significantly increased. A tamoxifen-inducible Axin2 CreERT2/+ ; R26R mTmG/+ reporter strain was then used to demonstrate that a population of long-lived Wnt-responsive odontoblasts, which secreted dentin throughout the life of the animal, were responsible for depositing new dentin in response to a superficial injury. Amplifying Wnt signaling in the pulp stimulates dentin secretion, and in the dentin injury model, we show that a liposomal formulation of human WNT3A protein passes through dentinal tubules and is capable of upregulating Wnt signaling in the pulp. These data provide strong proof of concept for a therapeutic pulp-capping material to stimulate Wnt signaling in odontoblasts and thus improve the pulp repair response.